Low‐power 10‐bit 100 MS/s pipelined ADC in digital CMOS technology - Anil Singh; Veena Rawat; Alpana Agarwal (IET Circuits, Devices and Systems, 2017)
A 10‐bit pipelined analogue‐to‐digital converter (ADC) at a sampling rate of 100 MS/s utilising only metal–oxide–semiconductor (MOS) transistors is presented and designed in 1.8 V 0.18 μm standard digital complementary MOS (CMOS) n‐well technology. The internal gain of value 2 of the intermediate stages is achieved by using a charge‐pump‐based concept that avoids the use of power‐area inefficient operational amplifier. All the capacitors are realised by capacitors implemented by metal–oxide–semiconductor field‐effect transistors (MOSCAPs) that allows easy integration with any inexpensive standard digital CMOS technology, and altogether giving low area‐power‐cost solution. A low DC gain CMOS differential amplifier in source follower configuration is used and low gain effects are calibrated digitally in the background. Peak differential non‐linearity (DNL) improves from −1/+0.27 least significant bit (LSB) to −0.43/+0.57 LSB and peak integral non‐linearity (INL) is reduced from −9.56/+9.3 LSB to within range of ±0.5 LSB after calibration. Also signal‐to‐noise plus distortion ratio (SNDR) and spurious‐free dynamic range (SFDR) increase to 65.4 and 72.08 dB, respectively, after calibration.